TRANFORMASI POLIMORFIK DAN KARAKTERISASI MIKROSTRUKTUR FASA TiO2 YANG DIHASILKAN MELALUI KALSINASI NANOPITA HIDROGEN TITANAT - Hari Sutrisno (Jurnal Sains Dasar, 2012)
Sodium titanates were synthesized by hydrothermal method using Ti(O2)O.2H2O as the starting material in 10 M NaOH at 150°C for 72 h. Hydrogen titanate nanoribbons were obtained by ion exchange of H+ for K+ in sodium titanates by 0.1 M HCl. TiO2 (B), anatase, and anatase-rutile mixture were obtained by the calcinations of hydrogen titanate nanoribbons for 2 h at 500, 700, and 900°c respectively. Hydrogen titanate nanoribbons were characterized by X-rays Diffraction (XRD), High Resolution Scanning Electron Microscopy (HRSEM) and High Resolution Transmition Electron Microscopy (HRTEM). Microstructure of pseudo-TiO2 (B), anatase, and rutile prepared by the calcinations of hydrogen titanates have been determinated in ab initio by the Two Stage Method from powder XRD data. Hydrogen titanates nanoribbons convert into pseudo-TiO2(B) then anatase and finaly rutile structures by heat treatment. Keywords: polymorphic transformation, microstructure characterization, titanium dioxide